Durability Probabilistic Evaluation of RC Structures Subjected to Chloride Ion - Han Seung Lee; Mohamed Ismail; Mohd Warid Hussin (Renewable Energy and Sustainable Development)
Chloride attacks concrete structures becoming a primary factor that deteriorates the durability of concrete structures. For this reason, research has been conducted on chloride ion penetration and diffusion. This research produced an accurate durability life prediction through reliability assessments and proposes a prediction method for the chloride ion diffusion coefficient of a concrete applied assessment program for reliability. As a result, test materials were fabricated using different admixtures and chloride ion diffusion coefficient was calculated by applying an RCPT test at each equivalent age. Based on these results, reliability prediction formulas were indicated through the reliability analysis for a durability life design using a Monte Carlo method. In addition, propriety was verified through comparisons and analysis using the proposed formula with the investigated data for chloride ion diffusion.